KAJIAN PSIKOLOGI SASTRA DALAM NOVEL TOPI HAMDAN KARYA AUNI FA - Missriani; Yanti, Asri; Agustina, Juaidah (Universitas PGRI Palembang, 2022)
Literary psychology is a field of study that examines literary works considered to reflect psychological processes and activities. This research questions how the intrinsic elements in the novel